PENGARUH KUALITAS PELAYANAN, STRATEGI IKLAN DAN PERSONAL SELLING TERHADAP KEPUTUSAN MENJADI NASABAH KOPERASI SIMPAN PINJAM (KSP) NIRWANA ARTA MANDIRI - I Made Irvan Widiatmika; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
The ups and downs of the number of decisions to become customers are caused by the many competitors from savings and loan cooperatives so that a good marketing strategy is needed to increase the decision to become a customer. Many factors influence the decision to become a customer including service, promotion, personal selling, company image, product, price, location and other factors, so these factors must be improved to achieve company goals. The purpose of this study was to determine and analyze the effect of service quality, advertising strategy and personal selling on the decision to become a customer of the Nirwana Arta Mandiri Savings and Loans Cooperative. Sampling was determined using purposive sampling technique with a total sample of 100 respondents. Data collection techniques using a questionnaire. The collected data were analyzed using multiple linear regression analysis. The results showed that service quality, advertising strategy and personal selling each had a positive and significant effect on the decision to become a customer of the Nirwana Arta Mandiri Savings and Loans Cooperative. Suggestions for future researchers are expected to be able to research with other variables, especially marketing in order to obtain more varied results and influence the decision to become a customer at KSP Nirwana Artha Mandiri.